2001
DOI: 10.1523/jneurosci.21-12-04469.2001
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Is Released in the Dorsal Horn by Distinctive Patterns of Afferent Fiber Stimulation

Abstract: Brain-derived neurotrophic factor (BDNF) is synthesized by small neuron cell bodies in the dorsal root ganglia (DRG) and is anterogradely transported to primary afferent terminals in the dorsal horn where it is involved in the modulation of painful stimuli. Here we show that BDNF is released in the rat isolated dorsal horn after chemical stimulation by capsaicin or electrical stimulation of dorsal roots. Capsaicin superfusion (1-100 M) induced a dose-dependent release of BDNF, measured using ELISA. The highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
232
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(247 citation statements)
references
References 63 publications
11
232
0
Order By: Relevance
“…It was therefore striking, when it was discovered that BDNF is normally produced by a subset of trkA positive nociceptors and that the number of trkA neurons making this factor is dramatically increased by increased NGF (Apfel et al, 1996;Michael et al, 1997). Indeed, BDNF could be shown to be released by activity in sensory neurons and its release is enhanced by elevated NGF levels that follow inflammation (Balkowiec and Katz, 2000;Lever et al, 2001). Thus, increased peripheral NGF leads to increased production and release of BDNF from the central synapses of nociceptors in the spinal cord, which may be critical for certain central sensitization events, especially those involving NMDA receptors .…”
Section: Mechanisms Of Ngf-dependent Mechanical Hyperalgesiamentioning
confidence: 99%
“…It was therefore striking, when it was discovered that BDNF is normally produced by a subset of trkA positive nociceptors and that the number of trkA neurons making this factor is dramatically increased by increased NGF (Apfel et al, 1996;Michael et al, 1997). Indeed, BDNF could be shown to be released by activity in sensory neurons and its release is enhanced by elevated NGF levels that follow inflammation (Balkowiec and Katz, 2000;Lever et al, 2001). Thus, increased peripheral NGF leads to increased production and release of BDNF from the central synapses of nociceptors in the spinal cord, which may be critical for certain central sensitization events, especially those involving NMDA receptors .…”
Section: Mechanisms Of Ngf-dependent Mechanical Hyperalgesiamentioning
confidence: 99%
“…Moreover, Hartmann et al (2001) found that different mechanisms regulate release of BDNF-GFP in response to high-frequency presynaptic stimulation and continuous KCl depolarization, respectively. Finally, studies from this and other laboratories demonstrated that release of native BDNF from sensory neurons (Balkowiec and Katz, 2000;Lever et al, 2001) or of adenovirally overexpressed BDNF (AdVBDNF) from hippocampal neurons (Gärtner and Staiger, 2002) can be regulated by the frequency and pattern of stimulation. However, mechanisms underlying activity-dependent secretion of native BDNF from hippocampal neurons have not been defined.…”
mentioning
confidence: 90%
“…The magnitude of native BDNF release from primary sensory neurons is regulated by the frequency and pattern of stimulation (Balkowiec and Katz, 2000;Lever et al, 2001). To determine whether similar mechanisms regulate activity-dependent secretion of BDNF from hippocampal neurons, we next examined the relationship between the pattern of stimulation and the magnitude of native BDNF release in hippocampal cultures.…”
Section: Short-term Patterned Electrical Stimulation But Not Short-tmentioning
confidence: 99%
“…Calcium oscillations reduce the effective threshold for transcription factor activation and thus gene expression (27,44,52,160). For example, BDNF, a neurotrophic factor implicated in many forms of neural plasticity, exhibits pattern-sensitive, activity-dependent synthesis (166), and release (11,125), at least in some types of neurons.…”
Section: The Stimulus Paradigm Is a Key Determinant Of Plasticitymentioning
confidence: 99%